Dating the Turning Points of Nordic Business Cycles. - Peter F. Christoffersen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2000)
When were the significant turning points in business activity in the Nordic countries during the last fourty years? How frequent, long, and sharp were the contractions? This paper provides answers to these questions by applying the Bry and Boschan (1971) algorithms, which have been used to analyze business cycle turns in several countries, in particular the United States. Applying the same methods for Nordic countries it is found that contractions were unusually long and frequent in Sweden, while expansions were unusually long in Finland and Norway. However, contractions were not necessarily sharper in Sweden when compared with the other Nordic countries. Surprisingly, not much evidence of a common Nordic cycle is found. It appears instead that Sweden and Denmark tend to mimic the downturns in the G-7 countries more closely than Finland and Norway.
Keywords: 330